Analyzing Reading-Related Activities In English Textbook For Grade VIII And How The Texts Are Exploited In The Classroom - Karisma Dewi, Luh Dina (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
Some students still have challenges in reading, such as pronunciation, identifying the text’s content, and accent. Then students did not participate actively since there is still limited activities of reading conducted during the learning process. This study aimed at analyzing reading-related activities that are available in English textbook used for grade 8 students in SMP Cipta Dharma Denpasar and observing how the texts are exploited by teacher in English class. The subject of this study was an English textbook used in the school and English teacher.This current research used qualitative descriptive analysis as the research methodology. The data collection was done through observation of the English textbook and the teacher’s strategy in conducting the learning in the classroom. In analyzing the data, this study is involving four processess including data collection, data reduction, data display, and conclusion (drawing/veryfying). From the analysis of the English textbook, the results showed there are several reading-related activities available in the textbook namely skimming/scanning, reference activity, lexical item activity, activating, inferring, and questioning. The most frequent exploitation of text done by the teacher are short-answer activities, searching-selecting, completing, and matching activities. Therefore, this study suggests more research regarding the texts exploitation done by English teacher in different levels of schools and classrooms.